Second‐look arthroscopic findings after CORA‐based leveling osteotomy. Issue 2 (8th September 2017) - Vasquez, Barbara; Hulse, Don; Beale, Brian; Kerwin, Sharon; Andrews, Chad; Saunders, Brian W.
Abstract: Objective: To describe the arthroscopic appearance of intra‐articular structures mid‐term (9 months) and long‐term (>12 months) after CORA‐based leveling osteotomy (CBLO). Study design: Case series. Animals: Dogs (n = 41) with second‐look arthroscopy of the stifle after CBLO for treatment of a cranial cruciate ligament (CCL) deficiency. Both stifles were re‐evaluated (stifles n = 42) in 1 dog. Methods: Medical records of dogs that had second‐look arthroscopy after CBLO were reviewed. Arthroscopic images of the femoral condyles were independently reviewed. The surgical report documented the integrity of menisci and articular cartilage of the tibial plateaus. Results: The population included 7 stifles with stable partial CCL tears, 35 stifles with complete CCL tears (n = 28), or incompetent partial CCL tears (n = 7). Median time to second look arthroscopy was 16 months (9‐24 months) for stable partial tears. The CCL remained intact in 6 stifles. The Outerbridge score of the articular cartilage of the femoral condyles was as 0 (6) or 1 (1). The articular cartilage of the tibial plateaus appeared normal in all stifles. Median time to second look arthroscopy of stifles with complete tears was 12 months (range, 9‐34 months). The caudal cruciate ligament was normal or mildly fibrillated. The appearance of the articular cartilage of the femoral condyles was scored as 0 or near normal (grade 1‐2) in all dogs. The articular cartilage of the tibial plateaus appeared normal, except in 1 dog with grade 4 lesion. Conclusion: CBLO results in minimal to no change in articular cartilage in at a median time of 14 months after surgery. Postoperative clinical lameness is often attributed to late onset meniscal pathology.